2021
DOI: 10.1155/2021/6628882
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Seepage and Deformation in Excavation of a Deep Foundation Pit under Water-Rich Fractured Intrusive Rock

Abstract: Water is one of the major risk sources in the excavation of deep-large foundation pits in a water-rich area. The presence of intrusive broken diorite porphyrite in the stratum aggravates the risk level of deep foundation pits. Based on a geological survey report and design documents of parameter information, MIDAS/GTS software was used to perform the numerical simulation of an engineering example of a deep foundation pit project of ultradeep and water-rich intrusion into the broken rock station of subway line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…He used MIDAS/GTS software to carry out numerical simulation on the example of subway deep foundation pit engineering. The results show that the deeper the water in the deep foundation pit, the greater the danger [ 5 ]. Bian et al found that in the excavation of deep foundation pits in subway stations, if the protective measures are not perfect, the safety of subway tunnels will be seriously threatened.…”
Section: Related Workmentioning
confidence: 99%
“…He used MIDAS/GTS software to carry out numerical simulation on the example of subway deep foundation pit engineering. The results show that the deeper the water in the deep foundation pit, the greater the danger [ 5 ]. Bian et al found that in the excavation of deep foundation pits in subway stations, if the protective measures are not perfect, the safety of subway tunnels will be seriously threatened.…”
Section: Related Workmentioning
confidence: 99%
“…According to the actual project, Yu [14] used Abaqus finite element software to simulate the construction steps for excavation of the foundation pits supported by large diameter ring beams and obtained the influence law of the foundation pit support system on the surrounding environment. Yuan [15] used MIDAS/GTS software to conduct a numerical simulation of a deep and large foundation excavation in a water-rich area and analyzed the distribution law of seepage in a deep foundation pit and the surface settlement law of the soil around a foundation pit during construction.…”
Section: Introductionmentioning
confidence: 99%
“…The excavation process had been studied by simulation method extensively. However, most of the case studies only focused on one aspect, accounting for either the rock and soil mechanical deformation of the foundation pit excavation [14][15][16] or ground surface settlement caused by the drawdown of groundwater level [17][18][19][20]. Few cases consider both types of deformation.…”
Section: Introductionmentioning
confidence: 99%